When Teams Fail to Self-Regulate: Predictors and Outcomes of Team Procrastination Among Debating Teams - Van Hooft, Edwin A. J.; Van Mierlo, Heleen (Frontiers in Psychology, 2018)
Models of team development have indicated that teams typically engage in task delay during the first stages of the team’s life cycle. An important question is to what extent this equally applies to all teams, or whether there is variation across teams in the amount of task delay. The present study introduces the concept of team procrastination as a lens through which we can examine whether teams collectively engage in unplanned, voluntary, and irrational delay of team tasks. Based on theory and research on self-regulation, team processes, and team motivation we developed a conceptual multilevel model of predictors and outcomes of team procrastination. In a sample of 209 student debating teams, we investigated whether and why teams engage in collective procrastination as a team, and what consequences team procrastination has in terms of team member well-being and team performance. The results supported the existence of team procrastination as a team-level construct that has some stability over time. The teams’ composition in terms of individual-level trait procrastination, as well as the teams’ motivational states (i.e., team learning goal orientation, team performance-approach goal orientation in interaction with team efficacy) predicted team procrastination. Team procrastination related positively to team members’ stress levels, especially for those low on trait procrastination. Furthermore, team procrastination had an indirect negative relationship with team performance, through teams’ collective stress levels. These findings add to the theoretical understanding of self-regulatory processes of teams, and highlight the practical importance of paying attention to team-level states and processes such as team goal orientation and team procrastination.